2016
DOI: 10.1017/s0144686x16000337
|View full text |Cite
|
Sign up to set email alerts
|

Who speaks up for Inés Fonseca? Representing violence against vulnerable subjects and the ethics of care in fictional narrative about Alzheimer's disease:Ahora tocad música de baile(2004) by Andrés Barba

Abstract: This paper studies the 2004 Spanish fictional novel by Andrés Barba, Ahora tocad música de baile, one of the first cultural texts dealing entirely with Alzheimer's disease to appear in Spain. It argues that the significance of Barba's fictional novel rests on two important issues: the ethics of representation of violence against vulnerable subjects and the ethics of care. The paper analyses how these two issues allow Barba to create a story in which the verbal and physical abuse to which the person living with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The interchangeability of the terms dementia and Alzheimer’s disease was also apparent in the research papers themselves. The titles of 21 papers suggested that they focused on the depiction of Alzheimer’s disease [ 26 , 27 , 29 , 32 , 35 , 38 , 39 , 42 , 43 , 46 , 53 , 63 65 , 68 – 70 , 72 , 77 , 80 , 83 ]. However, some of these used the terms dementia and Alzheimer’s interchangeably (e.g [ 24 , 32 , 43 , 69 , 70 ]).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The interchangeability of the terms dementia and Alzheimer’s disease was also apparent in the research papers themselves. The titles of 21 papers suggested that they focused on the depiction of Alzheimer’s disease [ 26 , 27 , 29 , 32 , 35 , 38 , 39 , 42 , 43 , 46 , 53 , 63 65 , 68 – 70 , 72 , 77 , 80 , 83 ]. However, some of these used the terms dementia and Alzheimer’s interchangeably (e.g [ 24 , 32 , 43 , 69 , 70 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, writing by people with dementia also included the living dead frame [ 38 ]. Following on from the notion that they are dead, people with dementia were also described as subhuman - ‘self that unbecomes’, ‘nonpersons’, ‘not human’ [ 35 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations